The effect of star chef image on reputation, familiarity, and loyalty - Sung-Man Ahn; Jae-Jang Yang (Global Business & Finance Review (GBFR), 2024)
Purpose: This paper explored the Star Chefs' images among customers who visit their restaurants in order to under-stand the effect of such images on familiarity, reputation, and loyalty. Design/methodology/approach: The study data were collected from the target customers of South Korean Star Chef restaurants. Representative South Korean Star Chefs appearing on South Korean TV programs who are running their own restaurants were contacted and told about the objective of this study. Of the nine Star Chefs contacted for cooperation, six Star Chef restaurants agreed to join this study. Findings: First, the Star Chef's image had a significant influence on familiarity and reputation. Second, the Star Chef's familiarity had a significant influence on reputation, and the Star Chef's familiarity had a significant influence on loyalty. Last, the Star Chef's reputation had a significant influence on loyalty. Research limitations/implications: This study is the image and reputation were examined by personifying the brand. This type of study could not include all the different human characteristics. Additionally, there are some difficulties in generalizing this study worldwide. Because there are only a few chefs that appear on TV programs in South Korea. Originality/value: The importance of service quality and environment has been highlighted in previous studies of restaurants, but studies of chefs who provide services are limited.
Keywords: 650; Star Chef; Image; Familiarity; Reputation; Loyalty